Improving cycling performance of Vanadium-based electrode deposited with poly(3,4-Ethylenedioxythiophene) for Lithium-Ion battery application - Mohd Abdah, Muhammad Amirul Aizat; Lee, Tian Khoon; Ahmad, Azizan; Sulaiman, Yusran; Dzulkarnain, Nurul Akmaliah; Mokhtar, Marliyana; Mohammad Khalid; Su’ait, Mohd Sukor (American Chemical Society, 2023)
Conducting polymers have attracted a considerable amount of interest as a high-performance electrode candidate for lithium-ion batteries (LIBs), which can substantially improve the electrical conductivity of the electrode by promoting electrical conduction pathways along the active materials. In this work, we have demonstrated the significant enhancement of carbon nanofibers/vanadium pentoxide using poly(3, 4-ethylenedioxythiophene) as dopant, denoted as (CNFs/V2O5/PEDOT) in electrochemical performance. CNFs/V2O5/PEDOT is successfully prepared via electrospinning, hydrothermal and subsequent electropolymerization processes. On the basis of experimental data, galvanostatic charge–discharge in half-cell of CNFs/V2O5/PEDOT revealed remarkably enhanced Li storage performance by exhibiting 520 mAh/g of initial discharge capacity at 2 mA/g, which is nearly two times higher than the CNFs/V2O5 electrode (270.4 mAh/g). However, the electrochemical properties of CNFs/V2O5/PEDOT electrode is dramatically degraded in the following cycles. To further understand the rapid degradation of CNFs/V2O5, the DEIS (in situ impedance analysis) approach is used as a faithful representation as a real battery system. The results indicated that degradation is originating from electrode pulverization upon volume expansion/shrinkage and unstable SEI formation during cycling. The DEIS studies manifested that CNFs/V2O5/PEDOT electrode could not withstand high potential when charge (>2.5 V). Conventionally, improvements in cycling performance were observed when the corrected cutoff voltages (1.0 to 2.5 V) were applied despite the high charging rate at a current density of 10 mA/g. It shows that CNFs/V2O5/PEDOT electrode can retain about 83 of the initial capacity as compared with CNFs/V2O5 (∼67 capacity retention) with enhanced charge transfer resistance (Rct) (25 Ω) after cycling, confirming that PEDOT could serve as a protective layer to prevent the surface side reactions of the electrodes with the electrolyte. This work suggests that CNFs/V2O5/PEDOT electrode could potentially serve as a promising material candidate for ultrafast charging of LIBs.